Enhancing Critical Thinking in Society 5.0: An Evaluation of High Order Thinking Skills (HOTS) in Secondary Education - Zahri, Triave Nuzila; Sari, Azmatul Khairiah; Sari, Resti Elma (International Journal of Research in Counseling and Education, 2023)
In the evolving landscape of Society 5.0, the imperative for students to think critically has become paramount. The acquisition of high order thinking skills (HOTS) plays a pivotal role in nurturing students to become independent, creative thinkers. These skills, encompassing analysis, evaluation, and the generation of innovative ideas, are essential for adapting to the dynamic demands of the modern era. However, the transition to HOTS-based learning poses challenges for students accustomed to conventional teaching methods. This study, conducted among 265 selected students from SMP Negeri 30 Padang using a stratified random sampling technique, employed a questionnaire for data collection. Descriptive statistical analysis revealed that 77% of students exhibited HOTS in performing tasks, 77% in answering exams, and 76% in actively engaging with the learning process. Moreover, gender disparities were observed in HOTS-based learning, with 74% of male students demonstrating proficiency compared to 79% of female students. The findings underscore the necessity for educational institutions to address the readiness of students for HOTS-based learning methodologies. Recognizing the gender-based variations in HOTS proficiency, schools are urged to implement targeted strategies to enhance students' critical thinking skills, ensuring optimal outcomes in the learning process. This research contributes valuable insights into the ongoing efforts required to cultivate HOTS-based learning environments in secondary education.